Sustainability of the Australian radiation oncology workforce: A survey of radiation therapists and radiation oncology medical physicists - Halkett, Georgia; Berg, M.; Breen, Lauren; Cutt, D.; Davis, M.; Ebert, M.; Hegney, D.; House, M.; Kearvell, R.; Lester, L.; Maresse, Sharon; McKay, Jan (Wiley-Blackwell Publishing Ltd., 2018)
Â© 2018 John Wiley & Sons Ltd This study aimed to determine and compare Radiation Therapists' (RTs') and Radiation Oncology Medical Physicists' (ROMPs') perspectives about their profession and workplace, satisfaction with career progression opportunities, and leaving the current workplace. RTs and ROMPs who were currently or had previously worked in Australia were invited to complete an online survey. Univariate and multivariate methods were used for analysis. Participants were 342 RTs and 112 ROMPs with estimated response rates of 14% and 26% respectively. Both professions rated workload poorly and identified the need for improvement in: communication between professions' members, support for junior staff/new graduates, staff morale, on-site training and multidisciplinary communication. RTs, more than ROMPs, perceived their profession was recognised and respected, but RTs were less likely to be satisfied with career progression/advancement, job promotion prospects and opportunities to specialise. At least 20% of RTs and ROMPs were thinking about leaving their workplace and 13% of RTs and 8% of ROMPs were thinking about leaving their profession. Different factors contributed to workforce satisfaction and retention within each profession. Staff satisfaction and career progression are critical to retain RTs and ROMPs. Further research is required to explore strategies to address workplace dissatisfaction, recruitment and retention.